Lifestyle in patients with hypertension from the Shoulder to Shoulder Foundation - Calderón Landívar , Ruth Elizabeth; Campos Silva, Teresa Lisbeth; López Gutiérrez, Girson Aaron; Chávez-Arizala , Jenrry Fredy (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Arterial hypertension (AHT) is defined as a disorder in which the blood vessels frequently have high tension, increasing the risk of cardiovascular, cerebral, and renal diseases, etc. Objective: To determine the lifestyles of patients with hypertension of the Hombro a Hombro Foundation, Santo Domingo, 2022. Methodology: The research is quantitative, data on the lifestyles of patients with arterial hypertension were collected, with a descriptive, cross-sectional level in which the collected data was stored and analyzed. The population consisted of 50 patients with arterial hypertension from the Shoulder to Shoulder Foundation. Results: Determining that within the healthy parameters are the physical condition, physical activity and sport; self-care and medical care; eating habits; the consumption of substances and some parameters on rest, although the last one could show that there is a small problem due to unhealthy practices. Conclusions: there are still patients who do not adhere to a new lifestyle, and work must continue to improve and treat as much as possible for the patient to adapt to this new stage, allowing him to be healthier